The burden of asthma, hay fever and eczema in adults in 17 countries: GAN Phase I study. Issue 3 (15th September 2022) - Mortimer, Kevin; Lesosky, Maia; García-Marcos, Luis; Asher, M. Innes; Pearce, Neil; Ellwood, Eamon; Bissell, Karen; El Sony, Asma; Ellwood, Philippa; Marks, Guy B.; Martínez-Torres, Antonela; Morales, Eva; et al.
Aims: Asthma, hay fever and eczema are three common chronic conditions. There have been no recent multi-country data on the burden of these three conditions in adults; the aims of this study are to fill this evidence gap. Methods: The Global Asthma Network Phase I is a multi-country cross-sectional population-based study using the same core methodology as the International Study of Asthma and Allergies in Childhood Phase III. It provides data on the burden of asthma, hay fever and eczema in children and adolescents, and, for the first time, in their parents/guardians. Results: Data were available from 193 912 adults (104 061 female; mean±sd age 38±7.5 years) in 43 centres in 17 countries. The overall prevalence (range) of symptoms was 6.6% (0.9–32.7%) for current wheeze, 4.4% (0.9–29.0%) for asthma ever, 14.4% (2.8–45.7%) for hay fever ever and 9.9% (1.6–29.5%) for eczema ever. Centre prevalence varied considerably both between countries and within countries. There was a moderate correlation between hay fever ever and asthma ever, and between eczema ever and hay fever ever at the centre level. There were moderate to strong correlations between indicators of the burden of disease reported in adults and the two younger age groups. Conclusion: We found evidence for a substantial burden of asthma, hay fever ever and eczema ever in the countries examined, highlighting the major public health importance of these diseases. Prevention strategies and equitable access to effective and affordable treatments for these three conditions would help mitigate the avoidable morbidity they cause. There is a substantial global burden of asthma, hay fever and eczema in adults, which represents a major global public health problem. Accessible, affordable, equitable and effective strategies are needed to reduce this burden across the life-course. https://bit.ly/3uBTQfl